Phylogenetic and biogeographic relationships of gerbil mice Eligmodontia (Rodentia, Cricetidae) in South America, with a description of a new species - Mares, Michael A.; Braun, Janet K.; Coyner, Brandi S.; van Den Bussche, Ronald A. (Zootaxa, 2008)
We present a systematic study of the genus Eligmodontia (sigmodontine rodents of the tribe Phyllotini) from Argentina, Bolivia, and Chile, based on molecular data. Phylogenetic relationships among 49 individuals were examined using nucleotide sequence data from the entire 1143 bp of the mitochondrial cytochrome-b gene. Unweighted parsimony, minimum evolution, maximum-likelihood (TrN+I+G), and Bayesian analyses revealed 2 major clades, representing Andean and non-Andean groups, and 6 minor clades, representing E. typus (lowland), E. typus (highland), E. morgani, E. puerulus, E. moreni, and E. hirtipes. E. typus (highland) is described as a new species based on combined data from the cytochrome-b gene, morphology, and karyology. The results indicate that the genus Eligmodontia is composed of a complex of species, most of which correspond to taxa that were described originally and each of which shows molecular cohesion within a limited geographic range. This species complex has relevance to current theories regarding the speciation patterns and the historical biogeography of South American sigmodontine rodents. The biogeographic history of the genus also is outlined.